(untitled) (Journal of the College of Education for Women, 2018)
This research was carried out to reveal the the technique of the recitation in this story including a preface, introduction, two chapters and the conclusion. the introduction consisted of the problem, significance , purpose and limitations of research. The preface included two paragraphs. The first included a meta-recitation of terminology and semantic. The second paragraph devoted to show the cultural identity of Hussein Rahim. The first chapter aimed to reveal the reality and the imaginary in the story of Na’lat Al Hakawaty (storyteller’s curse). The second chapter aimed to study the strange arguments in the story. The research concluded the conclusion by presenting the results for attaching them with the margins, and the references